INCREASE IN OPERATIONAL AVAILABILITY THROUGH THE APPLICATION OF LEAN MANUFACTURING - de Simone, Beatriz Greicyelle; Regattieri , Carlos Roberto (Revista Interface Tecnológica, 2022)
Nowadays, competitiveness is a basic requirement for the survival and expansion opportunities of a company, resulting from improvements in productivity and cost reduction, without affecting the quality of its products. This work presents the Lean Manufacturing management system and the SMED tool as an alternative to solve a common problem among companies: waste. In this article, we will demonstrate the application of this methodology to reduce the SETUP time of a production line, in order to increase the operational availability of a large and renowned food company through field research. The results obtained demonstrate that Lean Manufacturing is a powerful tool for increasing competitiveness and improving the quality of work of its employees.